Neurological Effects of Stimulants and Hallucinogens - Hass, Reece M.; Stitt, Derek (Seminars in Neurology, 2024)
In this article, we will discuss the history, pharmacodynamics, and neurotoxicity of psychostimulants and hallucinogens. The drugs discussed are widely used and have characteristic toxidromes and potential for neurological injuries with which the practicing clinician should be familiar. Psychostimulants are a class of drugs that includes cocaine, methamphetamine/amphetamines, and cathinones, among others, which produce a crescendoing euphoric high. Seizures, ischemic and hemorrhagic strokes, rhabdomyolysis, and a variety of movement disorders are commonly encountered in this class. Hallucinogens encompass a broad class of drugs, in which the user experiences hallucinations, altered sensorium, distorted perception, and cognitive dysfunction. The experience can be unpredictable and dysphoric, creating a profound sense of anxiety and panic in some cases. Recognizing the associated neurotoxicities and understanding the appropriate management is critical in caring for these patient populations. Several of these agents are not detectable by standard clinical laboratory analysis, making identification and diagnosis an even greater challenge.
Keywords: drugs of abuse; neurotoxicology; stimulants; hallucinogenic; toxicology